CHILI SEED MARKETING OPTIMIZATION STRATEGY IN AGRIBUSINESS COMPANIES IN SERDANG BEDAGAI REGENCY - Adriansyah Yoesoef; Ichpan Zulfansyah; Irshad Ahmad Reshi (CV. Radja Publika, 2024)
This study aims to formulate an effective marketing strategy to increase chili seed sales at the agribusiness company CV. Mitra Jaya, Serdang Bedagai Regency. The decline in sales indicates an inaccuracy in the implementation of marketing strategies. The research method used is a descriptive approach with data collection through interviews with key informants and analysis using the IFE, EFE, SWOT, and QSPM matrices. The results show that the company's main strengths lie in product quality and production experience, while the main weaknesses lie in limited promotion and marketing reach. The greatest opportunity comes from increasing chili consumption, while the main threat comes from increasingly fierce competition. Based on the SWOT analysis, several alternative strategies were obtained, and through QSPM it was determined that the priority strategies are developing digital-based promotions, maintaining product quality, and establishing partnerships with farmers. The implementation of these strategies is expected to improve the company's competitiveness and marketing performance.